Integrated Approach to Using Technology of Reclaimed Asphalt Pavement (RAP). (2017) - Lyubarskaya, M.A.; Merkusheva, V.S.; Osian, P.A.; Ilin, A.A.; Svintsov, E.S.
Abstract: The article analyses the problems of lack the system approach to using reclaimed asphalt pavement technologies (RAP) in Russia. The purpose of this article is to review global experience with RAP, identify common issues of implementation of this technology and develop methods to ensure a comprehensive approach to the use of RAP in Russia. The procedure of choosing a method of application RAP technology should addresses two main issues: cost-effectiveness and reducing the negative impact on the environment. Determining the most effective use of RAP technology is based on a combination of field and theoretical studies.